2008
DOI: 10.1097/scs.0b013e31818530a7
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Shapes and Related Differences in Nostril Forms

Abstract: Being aware of the morphologic differences in the nasal anatomy between men and women during the cosmetic rhinoplasty is essential because feminization of a male nose is not a very rare complication. Although there is no difference in the techniques of male and female rhinoplasty, the anthropometric differences have to be considered. This morphometric study evaluated the nasal shapes in both sexes and the related differences in the nostril forms. The nostril forms were separated into 4 main groups such as tear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 8 publications
3
10
1
Order By: Relevance
“…5 The sexual dimorphisms observed also said to have arisen due to the difference in the levels of testosterone between males and females, because testosterone was report earlier to cause a direct increase in the size and mass of muscles and bones, and thus causing differences in anthropometric parameters between the sexes. [6][7][8][9] This is in agreement with other studies by Olutu 10 Oladipo 11 who reported higher value (p<0.005) of all parameters in males compared to females but in contrast to study by Garadawa et al who found no significant sex differences 12 In this study, facial measurements were significantly higher in males than females which again demonstrated the existence of sexual dimorphism in this study. 8 This is similar to the study by Garadawa et al 9 and farkas et al 13 The mean upper facial height was longer than the mean lower facial height in both sexes and again similar to the findings of Garadawa et al 9 and farkas et al…”
Section: Discussioncontrasting
confidence: 35%
“…5 The sexual dimorphisms observed also said to have arisen due to the difference in the levels of testosterone between males and females, because testosterone was report earlier to cause a direct increase in the size and mass of muscles and bones, and thus causing differences in anthropometric parameters between the sexes. [6][7][8][9] This is in agreement with other studies by Olutu 10 Oladipo 11 who reported higher value (p<0.005) of all parameters in males compared to females but in contrast to study by Garadawa et al who found no significant sex differences 12 In this study, facial measurements were significantly higher in males than females which again demonstrated the existence of sexual dimorphism in this study. 8 This is similar to the study by Garadawa et al 9 and farkas et al 13 The mean upper facial height was longer than the mean lower facial height in both sexes and again similar to the findings of Garadawa et al 9 and farkas et al…”
Section: Discussioncontrasting
confidence: 35%
“…Therefore, it is unsuitable for absolute measurements, unless standardized procedures are followed to ensure a consistent, known magnification. However, it is ideally suited to the evaluation of proportions and shapes, as the magnification factor is eliminated [15]. …”
Section: Discussionmentioning
confidence: 99%
“…The characteristics and differences of the shapes of the nostrils have been studied in several racial groups [1315, 18, 21, 25, 26]. Among the classifications of nostrils, Farkas' classification divides the shape of nostrils by the angle between the right and left long nostril axes [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgeons should be aware of differences in values of the anthropometric parameters of a normal nose in relation to gender, although there is no difference in the techniques of rhinoplasty in men and women [20]. Feminization of the male nose, associated with lack of understanding the differences in the shape of the nose in relation to gender, is not a rare complication of rhinoplasty.…”
Section: Discussionmentioning
confidence: 99%